The Effect of Preliminary Treatment and Storage Time on the Quality of Infused Water Drinks of Butterfly Pea Flower (Clitoria ternatea), Siamese Oranges (Citrus nobilis), and Mint Leaves (Mentha piperita L.) - Salsabila, Aurellia; Ulya Sarofa; Andre Yusuf Trisna Putra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Infused wateris a natural alternative drink that contains various vitamins. In this research, an infused water drink will be made made from butterfly pea flowers, Siamese oranges and mint leaves. The aim of this research is to analyze the effect of pretreatment and storage time on the quality of the infused water produced and to identify the best treatment between pretreatment and storage time based on the physicochemical, microbiological and organoleptic characteristics of infused water drinks. This research used a completely randomized design (CRD) with a factorial pattern with two factors and three replications. Factor I is storage temperature (room temperature (27°C), refrigerator temperature (5°C), and room temperature that has been pasteurized (60°C for 15 minutes)). Factor II is storage time (1 hour, 3 hours and 6 hours). If there is a real difference, the further test will be continued with 5% DMRT. The best treatment results were obtained in the pre-pasteurization treatment at room temperature with a storage time of six hours which produced infused water with valuepH 5.257; vitamin C 19.57 mg/100g; antioxidant capacity (IC50) 2.187; total acid 0.312%; total phenol 1,261 mgGAE/gr; total plate count 1,950 Log CFU/ml; color preference score 3.80; aroma preference score 3.6; taste preference score 3.45.